2020
DOI: 10.1177/1049909120969128
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Asian Indian Americans’ Knowledge and Attitudes Toward Hospice Care

Abstract: Background: Previous research has found racial differences in hospice knowledge and misconceptions about hospice care, which may hinder access to hospice care. Asian Indians are a rapidly growing population in the United States, yet limited research has focused on their beliefs toward end-of-life care. This project investigates Indian Americans’ knowledge of and attitudes toward hospice care and advance care planning. Procedures: A cross-sectional design was employed using surveys about participants’ knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Possibly, lack of awareness is a more important factor than formal education in increasing hospice acceptability as studies including this one have shown negative perspectives towards hospice despite high education levels. 20 Findings also reveal the importance of the home as a private space among South Asians, that needs to be navigated sensitively by healthcare providers. The present study found that even home hospice was rejected by some participants, similar to hesitance towards hospice staff home visits expressed by nearly 44% of participants in another study.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Possibly, lack of awareness is a more important factor than formal education in increasing hospice acceptability as studies including this one have shown negative perspectives towards hospice despite high education levels. 20 Findings also reveal the importance of the home as a private space among South Asians, that needs to be navigated sensitively by healthcare providers. The present study found that even home hospice was rejected by some participants, similar to hesitance towards hospice staff home visits expressed by nearly 44% of participants in another study.…”
Section: Discussionmentioning
confidence: 96%
“…The present study found that even home hospice was rejected by some participants, similar to hesitance towards hospice staff home visits expressed by nearly 44% of participants in another study. 20 A systematic review of palliative care among the South Asian diaspora similarly reported about the home as a place for comfort where rituals, privacy, spiritual and personal cleanliness, a sense of security and being surrounded by family were maintained, in contrast to a hospital or hospice where these considerations were often not met. 2 Studies among the South Asian diaspora about palliative care provide context to our findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations